On the infinite powers of large zero-dimensional metrizable spaces - Medini, Andrea (Topology Proceedings, 2025)
We show that X^λ is strongly homogeneous whenever X is a non-separable zero-dimensional metrizable space and λ is an infinite cardinal. This partially answers a question of Terada, and improves a previous result of the author. Along the way, we show that every non-compact weight-homogeneous metrizable space with a π-base consisting of clopen sets can be partitioned into κ many clopen sets, where κ is the weight of X. This improves a result of van Engelen.